Measuring Online Battery AC Resistance Using a DC-DC Converter With Time and Frequency Hybrid Method - Seong-Jong Kim; Hwa-Pyeong Park; Tae-Hwan Jin; In-Jun Lee (IEEE Access)
The estimation of battery state is important for ensuring the stability of batteries. The AC resistance of a battery is one of the factors used to estimate the battery state, and is measured using a Fast Fourier Transform (FFT), a technique that analyzes the frequency components. The power converter can implement the dual functionality of power conversion and online AC resistance measurements and achieve high cost-effectiveness with the addition of only a control algorithm. However, the high FFT resolution in a Digital Signal Processor (DSP) requires a long computation time and Random-Access Memory (RAM) to process large amounts of data. Therefore, it is difficult to measure low-frequency ranges using AC resistance calculations based on the FFT. In this study, a time- and frequency-domain hybrid measurement method to enhance low-frequency AC resistance measurements with the desired frequency resolution is proposed. This study investigates frequency resolution in the low-frequency range using time- and frequency-domain measurement methods. The operational principle of the proposed method was analyzed to design a measurement algorithm. The experimental results verified the performance of the proposed method by measuring the AC resistance of a battery within the desired frequency range.